Agile Transformation in Real Estate: A Case Study of Extreme Programming Adoption for Vendor Management - Denny Jean Cross Sihombing (Jurnal Info Sains : Informatika dan Sains, 2023)
This research explores and implements innovative solutions for the property management industry, focusing on developing an apartment vendor management application. Adopting the Extreme Programming (XP) method, this research resulted in an adaptive and responsive software development approach. The development phase involved intensive planning, iterative development, and close monitoring to ensure the quality and effectiveness of the application. The application gradually increased its functionality using an iterative delivery process, allowing property management and vendors to adopt new features immediately. The feedback phase played a crucial role in refining and improving the application through iterative review sessions and user feedback collection. The study results include increased operational efficiency of property management, improved quality of service to apartment residents, and innovative contributions through the application of the XP model. With an adaptive development cycle, this research provides a foundation for developing similar applications in the property management industry. This research not only illustrates practical solutions to software development challenges but also contributes to improving the methodologies and practices of the property management industry. Adopting this development model can positively impact the operational efficiency, service quality, and adaptability of the property management industry. As a first step, this research paves the way for further research addressing future challenges and continuously improving how property management is implemented through software innovation.